Need for a continuing education program for toxoplasmosis control - Bresciani, Katia Denise Saraiva [UNESP]; Cardia, Daniel Fontana Ferreira [UNESP]; Camossi, Lucilene Granuzzio [UNESP]; Galvão, André Luiz Baptista [UNESP]; Vasconcellos, Amanda Leal de [UNESP]; Santos, Rodrigo Rabelo dos [UNESP]; Santos, Thaís Rabelo dos [UNESP]; Soares, José Antonio (Science Publishing Group, 2013)
The Toxoplasma gondii infection is very important from the point of view of public health and affects almost all homeothermic animal species, including birds and mammals. In this study, thirty teachers from elementary schools in the northwest area of the state of São Paulo, Brazil, were interviewed about toxoplasmosis. Their students frequented of first to fourth series of the fundamental teaching. The questionnaire with closed questions were: 1) is the cat the main transmitter of toxoplasmosis in humans?; 2) If the cat can transmit toxoplasmosis, how happens?; 3) “If the dog can transmit toxoplasmosis, how happens?”; Is there any other way to acquire toxoplasmosis?; If there are other means of transmission, which can be? After this stage, lectures of short duration were supplied about this disease and reapplied the interview form. The data were analyzed with base in descriptive statistics. We found that there was an assimilation of the concepts on the control of toxoplasmosis by the teachers. In conclusion, there is the need of implanting one continuing education program for the community in general directed to the improvement of basic concepts of toxoplasmosis control.
Keywords: Toxoplasma gondii; Education; Prevention